Quality aspects of some value added seaweed food and functional food products - Sarkar, Md Shirajul Islam; Kamal, Md; Hasan, Muhammad Mehedi; Hossain, Md Ismail (Fundamental and Applied Agriculture, 2019)
Culture of seaweed is expanding globally due to wide range application of seaweeds including human consumption as nutritious food. Despite the availability of naturally occurring seaweeds, utilization is scarcely noticed in Bangladesh. Therefore, some value added seaweed food and functional food products were experimentally manufactured and those products were found to be promising for commercial production. Proximate composition and shelf life determination by organoleptic evaluation were conducted on four value added seaweed food products viz., seaweed jelly, soup, ice cream, curd and two functional food products viz., seaweed singara, samosa. Crude protein, lipid, moisture and ash content of above mentioned food and functional foods items were analyzed. To study shelf life, two sets of sample; each set of sample included previously mentioned 4 value added seaweed food items and 2 value added seaweed functional food items stored both in ambient con- dition and in freezer at −18 °C were investigated for 1 month. Crude protein content of seaweed jelly, soup, ice cream and curd was 8.71%, 9.04%, 14.96% and 16.60%; lipid content was 6.76%, 12.67%, 10.33% and 1.10%; moisture content was 42.75%, 56.94%, 51.68% and 58.06%; ash content was 19.05%, 16.27%, 8.02% and 9.10%, respectively. Average proximate composition value of seaweed singara, samosa was found respectively as 9.80% and 10.01% crude protein, 6.88% and 6.17% lipid, 32.08% and 27.44% moisture, 13.20% and 10.01% ash. All value added seaweed food and functional food prod- ucts kept open in ambient condition had a shelf life of not more than three days. Shelf life of seaweed food and functional foods in freezer was at least 1 month. Determination of optimum use of seaweeds in product develop- ment, spoilage mechanism, development of more new products, effect of these products on human health, seaweed culture technique etc. should be investigated in future.